Effects of varied inundation characteristics on early life stages of a salt marsh plant - Wang, Qing; Luo, Meng; Cui, Baoshan; Chen, Cong; Xie, Tian; Li, Xia; Lu, Feng (Frontiers in Marine Science, 2024)
Tidal inundation is a major stress in salt marshes that regulates the patterns of plant distribution and the associated functions provided by vegetation communities. Usually, frequency is used to represent inundation intensity and can be estimated using elevation. However, frequency is only a statistical indicator of tidal inundation conditions during a given period, which ignores many details of tidal inundation characteristics based on a single tidal event. On the scale of a single tidal event, duration and water depth are important characteristics for describing inundation conditions, which vary along the elevation gradient. The frequency of tidal events of a specific duration and water depth also varied. To unravel the impact of varied inundation characteristics on the key life stages of a foundation plant, we designed an experiment with varied inundation treatments of different frequencies, durations, and depths. Our results showed that the frequency, duration, and depth of inundation events significantly influenced seed emergence, seedling survival, and growth. Stress can be strengthened by a higher frequency with a longer duration and larger depth. Among these factors, frequency had a dominant impact, followed by duration and water depth. Specifically, there is a trade-off between frequency, duration, and depth, suggesting that an inundation event with shallower depth and/or shorter duration would reduce the stress from higher frequency. The findings fill a gap in the loss of details of varied inundation characteristics on plant establishment on a fine scale. Further, it will help explicit inundation stress more accurately and clearly and provide important implications for stress relief solutions in coastal ecological restoration.